Efficacy of free and encapsulated Bacillus lichenformis strain SL10 on degradation of phenol: A comparative study of degradation kinetics. (15th July 2017) - Chris Felshia, S.; Aswin Karthick, N.; Thilagam, R.; Chandralekha, A.; Raghavarao, K.S.M.S.; Gnanamani, A.
Abstract: The present study exemplifies phenol degradation efficacy of the free and encapsulated bacterial isolate, explored the degradation kinetics and storage stability in detail. In brief, isolation, identification and phenol degradation potential of the bacterial made from wastewater treated sludge samples. The organism identified as B . licheniformis demonstrates phenol degradation at a concentration more than 1500 ppm. Optimization of environmental parameters reduces the time taken for degradation considerably. The organism has further been encapsulated using whey protein and the efficacy of encapsulated species suggested that encapsulation protects the cells from high concentration of phenol and at the same time expedite the degradation of the chosen pollutant at appreciable level. The encapsulated species effectively degrade 3000 ppm concentration of phenol within 96 h of incubation. Both pH and temperature stability observed in the encapsulated species suggests the effectiveness of the encapsulation. The encapsulated cells displayed storage stability for a four week period at 4 C and reusability up to three exposures. Degradation effected through intracellular catechol 2, 3 dioxygenase. In conclusion, encapsulation of B . licheniformis (i) protects the cells from direct exposure to toxic pollutants; (ii) facilitates the field scale application and (iii) eliminate the practical difficulties in handling wet biomass in field application and assures the best possible way of remediating the phenol contaminated soil. Highlights: B . licheniformis exhibits phenol degradation at concentration >1500 ppm. Encapsulation of B . licheniformis enhances degradation efficacy compared to free cells. Encapsulated bacterial species exhibits extended period of storage stability. Encapsulated species exhibit appreciable reusability. Encapsulated species suitable for remediation.